2005
DOI: 10.1021/la0509089
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Freely Suspended Membrane via a Combination of Interfacial Reaction and Wetting

Abstract: Applying poly(ethoxysiloxane) (a liquid non-water-soluble polymer that can be hydrolyzed and cross-linked by diluted acids) to an air/pH 1 water interface gave rise to thin homogeneous solid layers. These layers were strong enough to be transferable to electron microscopy grids with holes of dimensions up to 150 microm and covered the holes as freely suspended membranes. No homogeneous layers were formed at an air/pH 5 water interface. Brewster angle microscopy images show that the poly(ethoxysiloxane) is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…It was earlier demonstrated that PEOS does not wet the water surface at the initial stage of the contact. 28 During the hydrolysis, the solubility of PEOS in hydrocarbon is reduced and its affinity to water increases. Therefore, the structure of hydrolyzed PEOS resembles that of the amphiphilic surfactant molecules.…”
Section: Resultsmentioning
confidence: 99%
“…It was earlier demonstrated that PEOS does not wet the water surface at the initial stage of the contact. 28 During the hydrolysis, the solubility of PEOS in hydrocarbon is reduced and its affinity to water increases. Therefore, the structure of hydrolyzed PEOS resembles that of the amphiphilic surfactant molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Monomeric silanes partially substituted with ethylene glycols are expected to be amphiphilic; however, no information on their assembly in water is available, probably due to their high water solubility and too fast hydrolysis. Therefore, we have chosen a strategy to modify a bulky silica precursor polymer – hyperbranched polyethoxysiloxane (PEOS),7 which possesses much lower water solubility and hence a rather slower hydrolysis rate than the monomer tetraethoxysilane, and shows clear advantages for design of complex silica materials 8. As PEOS contains many terminal ethoxy groups, the substitution degree (subsequently the amphiphilicity) can be fine‐tuned in a broad range.…”
Section: Methodsmentioning
confidence: 99%
“…It has a lower solubility in water and lower hydrolysis rates in comparison to tetraethoxysilane. Owing to these features, this polyethoxysiloxane was used as a precursor for the hydrolytic synthesis of silica membranes [123] and mesostructured silica particles [124][125][126].…”
Section: Siloxanes By Nhsg Condensations Piers-rubinsztajn Reactionmentioning
confidence: 99%